From Intervention to Partnership—Prospects for Development Partnership in Solomon Islands after the RAMSI. Issue 2 (4th June 2014) - Barbara, Julien
Abstract This article considers prospects for effective development partnership in Solomon Islands following the transition of development assistance from the Regional Assistance Mission to Solomon Islands (RAMSI) to bilateral donors in 2013. It focuses on the shifting nature of Australian aid that has transitioned from an interventionary approach under RAMSI to a partnership‐based approach under the bilateral program. Prospects for partnership in Solomon Islands are complicated by issues of state fragility, political instability and aid dependency that undermine local ownership and alignment. While the rhetoric of partnership guided RAMSI transition, Australia's post‐RAMSI aid responds to these challenges through a hybrid approach incorporating partnership and interventionary modalities. This hybrid approach reflects Australia's role in the co‐production of sovereignty in Solomon Islands. Recognition of the hybrid nature of Australian aid, and, by implication, Australia's 'ownership' of development problems in Solomon Islands, will be important to the effectiveness of future support.